From Undereating to Overeating: Family Survival Strategies and Their Consequences - Kseniya Novgorodova (Психология и Психотерапия Семьи)
The article provides an overview of the multigenerational transmission process of eating behaviors and habits in Russia. During the mass hunger and food shortages in the 20th century people in Russia learned certain dietary patterns and food psychology which have been repeated in multiple generations. While eating norms shifted, the attitudes to food consumption have become deeply entrenched over years and may lead to an unhealthy relationship with food, like emotional eating, overeating and other eating disorders. The article describes two diagnostic therapeutic tools developed by the author: a focused genogram and the "Family Food Roles" questionnaire. Both are aimed at revealing multigenerational patterns that affect food behaviors and habits. These therapeutic tools foster counselor competencies in systemic family therapy for eating disorders and address the most appropriate assessment options for patients.